Gestión de inventario en la Ferretería Ferricap de la ciudad de Babahoyo - Vite Villamar, Julexy Brigitte (2020)
Today there are several organizations that make a mistake by not giving importance to controlling their inventories, underestimating the scope that these current assets have in optimizing their profits. Managing inventory is essential in commercial companies because it depends on its being efficient in order to achieve the business objectives set, inventory management is an important factor in the strategic management of any company, the tasks corresponding to it lie in the determination of the registration, rotation and classification methods determined by the control method to seek coordination and efficiency in the administration of the materials necessary for the commercial activity. The investigation called "Inventory Management in the Ferricap Hardware Store of the City of Babahoyo" aimed to identify the factors that cause an inadequate inventory management in said establishment and how the administration is managed by the owner as administrator of the hardware store it influences its performance. The existing problems in the Ferricap hardware store were addressed based on inventory management, the same that appear in the development. The Methodology used in this study was qualitative, the research method being inductive, the techniques and instruments used to collect more information were: an interview and surveys, obtaining results that allowed us to reach a general conclusion of the present case study, the same that was supported with bibliographic references which helped to understand in a scientific way the depth of this research.